Covid-19 Induced Anxiety and Depression in Healthcare Workers: Experiences of a Developing Country - Uzma Ghori; Sana Ansari; Erum Memon; Muhammad Osama Rehman Khalid; Shumaila Shabbir (ziauddin University, 2024)
Background: Healthcare workers all over the world are suffering physically, mentally and emotionally due to the Covid-19 pandemic. While psychological effects may be more pronounced in a country like Pakistan where such disorders are still considered taboo and remain unattended. The study aimed to identify the prevalence and association of anxiety and depression in healthcare workers in a tertiary care hospital in Karachi during Covid-19 pandemic. Methods: A descriptive, cross sectional study was performed from 1st June-31stAugust 2020 on n=361 healthcare staff. General Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) tools were used to assess for anxiety and depression respectively. Association between demographic variables age, gender, education, designation, work experience, Covid-19 exposure with anxiety and depression was assessed using the Chi-squared test with p ≤ 0.05 was considered statistically significant. Results: Anxiety 221(61.5%) and depression 276(76.9%) were more common in doctors compared to other health care workers. The prevalence of severe anxiety 248(69.2%) and severe depression 276(76.9%) was significantly higher in males. Both anxiety and depression were more common with less than 2 years of work experience (p=0.00). Association between years of work experience was similar, with people having less than 2 years of work experience feeling more anxiety (p=0.012) and depression (p=0.003). Conclusion: Doctors working with Covid-19 patients are more prone to severe anxiety and depression. Early identification and supportive care are essential to ensure that the clinical and para medical staff members assigned to patient care has access to both physical and mental health services. Keywords: Covid-19; SARS CoV-2; Anxiety; Depression; Generalized Anxiety Disorder; Patient Health Questionnaire.